2021
DOI: 10.1002/asi.24539
|View full text |Cite
|
Sign up to set email alerts
|

“There is a gorilla holding a key on the book cover”: Young children's known picture book search strategies

Abstract: There is no information search system can assist young children's known picture book search needs since the information is not organized according to their cognitive abilities and needs. Therefore, this study explored young children's known picture book search strategies and extracted picture book search elements by simulating a search scenario and playing a picture book search game. The study found 29 elements children used to search for known picture books. Then, these elements are classified into three dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
(68 reference statements)
0
0
0
Order By: Relevance
“…Consequently, the process of visual perception encompasses not only a fundamental psychological mechanism but also a subjective experience delineating how information is gathered and identified through mental models, which are influenced by object traits and past experiences (Yu, 2012). Studies have shown that when children search for familiar books, they frequently use visual elements, such as book titles, covers, story characters and illustrations, as search aids (Wang et al, 2022). However, when confronted with multiple visual stimuli, children may become overwhelmed.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the process of visual perception encompasses not only a fundamental psychological mechanism but also a subjective experience delineating how information is gathered and identified through mental models, which are influenced by object traits and past experiences (Yu, 2012). Studies have shown that when children search for familiar books, they frequently use visual elements, such as book titles, covers, story characters and illustrations, as search aids (Wang et al, 2022). However, when confronted with multiple visual stimuli, children may become overwhelmed.…”
Section: Introductionmentioning
confidence: 99%